An N‐Heterocyclic‐Carbene‐Derived Distonic Radical Cation. (30th January 2020) - Gallagher, Nolan M.; Ye, Hong‐Zhou; Feng, Shuting; Lopez, Jeffrey; Zhu, Yun Guang; Van Voorhis, Troy; Shao‐Horn, Yang; Johnson, Jeremiah A.
Abstract: We present the discovery of a novel radical cation formed through one‐electron oxidation of an N‐heterocyclic carbene–carbodiimide (NHC–CDI) zwitterionic adduct. This compound possesses a distonic electronic structure (spatially separate spin and charge regions) and displays persistence under ambient conditions. We demonstrate its application in a redox‐flow battery exhibiting minimal voltage hysteresis, a flat voltage plateau, high Coulombic efficiency, and no performance decay for at least 100 cycles. The chemical tunability of NHCs and CDIs suggests that this approach could provide a general entry to redox‐active NHC–CDI adducts and their persistent radical ions for various applications. Abstract : Ein persistentes distonisches Radikalkation wurde durch Ein‐Elektronen‐Oxidation eines NHC‐Carbodiimid‐Addukts (NHC=N‐heterocyclisches Carben) mit Pyrensubstituenten hergestellt. Der Einsatz dieser Verbindung in einer organischen Redox‐Flow‐Batterie wurde demonstriert. Die Studie liefert eine Grundlage für die Entwicklung neuartiger redoxaktiver NHC‐CDIs für verschiedene Anwendungen.